2021
DOI: 10.1002/ps.6404
|View full text |Cite
|
Sign up to set email alerts
|

Zoxamide accumulation and retention evaluation after nanosuspension technology application in tomato plant

Abstract: BACKGROUND: Low water solubility of pesticide requires formulations with high levels of stabilizers and organic solvents. Moreover, only 0.1% of the applied pesticides formulation reaches the target, while 99.9% spreads in the surrounding environment. Therefore, there is the need for more efficient and environmentally sustainable alternatives. RESULTS: Zoxamide (ZO) nanosuspension was prepared through a media milling technique by using the stabilizer polysorbate 80. The thin and acicular crystals obtained, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…previously described that NS could improve the deposition and accumulation of zoxamide on tomato plants. 30 A recent work also revealed that the uptake of nano-scale fungicide by the fungal pathogen Botrytis cinerea was approximately twice that of the micron-scale fungicide. 41 The results of our study support the application of NS in pesticide delivery, which could stimulate the development of key technology and products that can reduce the dosage and increase the efficiency of herbicides.…”
Section: Deposition and Uptake Of Quinclorac On Barnyardgrassmentioning
confidence: 99%
See 1 more Smart Citation
“…previously described that NS could improve the deposition and accumulation of zoxamide on tomato plants. 30 A recent work also revealed that the uptake of nano-scale fungicide by the fungal pathogen Botrytis cinerea was approximately twice that of the micron-scale fungicide. 41 The results of our study support the application of NS in pesticide delivery, which could stimulate the development of key technology and products that can reduce the dosage and increase the efficiency of herbicides.…”
Section: Deposition and Uptake Of Quinclorac On Barnyardgrassmentioning
confidence: 99%
“…26,27 To date, studies on NS mainly focus on wettability, retention and adhesion on the leaf surface and bioactivity against insects and fungi, 23,28,29 as well as its ability to increase deposition and accumulation. 30 Nevertheless, relevant reports on the use of NS to deliver herbicides are rare. In addition, few studies have focused on the deposition and uptake of NS on weeds, which is currently limiting their application in sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…25 Corrias et al produced a zoxamide nanosuspension with a particle size of 227 nm by a media milling technique, which increased pesticide water solubility and deposition and accumulation on tomato plants. 26 Suresh et al fabricated a nanopermethrin by solvent evaporation from an oil-in-water microemulsion. The nanopermethrin was 3 times more toxic to Aedes aegypti than the microparticular permethrin.…”
Section: Introductionmentioning
confidence: 99%
“…The fenpropathrin nanoemulsions prepared by Wei et al exhibited higher stability and insecticidal activity to Helicoverpa armigera, but lower toxicity to earthworms and L02 cells . Corrias et al produced a zoxamide nanosuspension with a particle size of 227 nm by a media milling technique, which increased pesticide water solubility and deposition and accumulation on tomato plants . Suresh et al fabricated a nanopermethrin by solvent evaporation from an oil-in-water microemulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Chin et al produced a carbendazim nanosuspension via media milling which exhibited a superior stability and a 13.5% increase in insecticidal efficiency over a micron-sized suspension [ 24 ]. Francesco et al prepared a zoxamid nanosuspension using the same method and increased the solubility 1.6-fold compared to the SC formulation while improving the deposition and retention abilities of the active ingredient on tomato plants [ 25 ]. In our previous work, we successfully constructed lambda–cyhalothrin and abamectin nanosuspensions using melt emulsification–high-pressure homogenization and wet milling methods, proving the effectiveness of nanotechnology for enhancing the dispersibility and biological activity of poorly soluble pesticides [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%